Removal of Horizontally Impacted Mandibular Third Molars Using the Three-Piece or T-Shaped Tooth Sectioning Method - He, Xianyi; Gao, Yichen; Shen, Jie; Pan, Qing; Chen, Junliang; He, Yun (Journal of oral and maxillofacial surgery, 2024)
The extraction of horizontally impacted mandibular third molars (HM3) can be a complicated surgery. Appropriate tooth sectioning methods can reduce the operation time and postoperative complications. The current study compares operative time and postoperative pain between HM3 removed using the three-piece or T-shaped tooth sectioning techniques. A randomized single-blind prospective clinical trial on HM3 extraction was carried out between June and December 2022 in the Department of Oral and Maxillofacial Surgery, the Affiliated Stomatological Hospital, Southwest Medical University. Patients with local or systemic infection, poor oral hygiene, and systemic disease were excluded. The predictor variable was the tooth sectioning method. The subjects were randomized to a three-piece or T-shaped group. The primary outcome variables were the operative time and postoperative pain measured using a visual analog scale (VAS). The secondary outcome variables were the rates of primary bleeding, mouth opening reduction, swelling, patient satisfaction measured using a VAS, and quality of life measured using a postoperative symptom severity scale. The covariates included age, sex, side and classification of HM3, and the relationship of HM3 to the inferior alveolar nerve canal. The data were analyzed using the independent samples t-test, paired t-test, χ2, and rank sum test. A significance level set at P < .05. The sample included 60 patients in the three-piece group and 66 patients in the T-shaped group. The operative time of the three-piece group (14.73 ± 3.21 minutes) was shorter than that of the T-shaped group (19.25 ± 4.29 minutes) (P < .05). On days 3 and 7, VAS of pain were 2.24 ± 1.89 and 0.15 ± 0.40 in the three-piece group and 3.95 ± 2.44 and 0.48 ± 0.68 in the T-shaped group (P < .05). The VAS of patient satisfaction in the three-piece group (6.05 ± 1.29) was better than the T-shaped group (4.90 ± 1.05) on day 7 (P < .05). The three-piece tooth sectioning for HM3 removal was associated with shorter duration, slighter postoperative symptoms, and higher patient satisfaction and may be considered as a recommended practice for dentists.